Isolamento e criopreservação de folículos pré-antrais caninos - Alves, Kele Amaral (2010)
The aim of this study was evaluate the canine preantral follicles after mechanical isolation procedures on different sectioning intervals, and of cryopreservation with the cryoprotectants glycerol and ethylene glycol. The isolation methodology used a tissue chopper device programmed on two thicknesses (250 e 500 μm) with the purpose to evaluate which provide a satisfactory number of structures preserving its integrity. The number of isolated follicles did not statistically differed between the tested thicknesses, being 25200 for 250 μm and 11000 μm (p=0,08). Viability and quality, measured by follicular membrane integrity and granulous cells presence, showed better results in the group of follicles isolated of 500 μm thicknesses. The following experiment submitted canine preantral follicles mechanically isolated to viability assay with propidium iodide dye, under the following procedures: after isolation (control group), after exposure period with glycerol or ethylene glycol on 1,5 or 3M (toxicity test), and after freezing/thawing with cryoprotectants at two different concentrations. On the toxicity test only the group that used ethylene glycol at 1,5 M did not shown significant reduction of viability (51,5%) compared with control group (63,2%). After cryopreservation, the follicular viability was significantly lower in all groups, being, 12% for glycerol at 1,5 M, 15,5% for ethylene glycol at 1,5 M, 14% for glycerol at 3 M and 28% for ethylene glycol at 3 M. This study concludes that ethylene glycol demonstrated the best results after the exposure period and freezing/thawing procedures.